Dexmedetomidine Mitigated NLRP3-Mediated Neuroinflammation via the Ubiquitin-Autophagy Pathway to Improve Perioperative Neurocognitive Disorder in Mice - Zhang, Lieliang; Xiao, Fan; Zhang, Jing; Wang, Xifeng; Ying, Jun; Wei, Gen; Chen, Shoulin; Huang, Xiangfei; Yu, Wen; Liu, Xing; Zheng, Qingcui; Xu, Guohai; et al. (Frontiers in Pharmacology, 2021)
Background Surgery and anesthesia-induced perioperative neurocognitive disorder (PND) are closely related to NOD-like receptors (NLR) family, pyrin domain containing 3 (NLRP3) inflammasome microglia inflammatory response. Fewer NLRP3-targeting molecules are currently available in the clinic to reduce the incidence of postoperative delirium. The present study showed that dexmedetomidine (DEX ) reduced the production of cleaved caspase1 (CASP1) and destroyed the NLRP3–PYD And CARD Domain Containing(PYCARD)–CASP1 complex assembly, thereby reducing the secretion of IL-1 interleukin beta (IL-1). DEX promoted the autophagy process of microglia and reduced NLRP3 expression. More interestingly, it promoted the ubiquitination and degradation of NLRP3. This study demonstrated that DEX reduced NLRP3-mediated inflammation through the activation of the ubiquitin-autophagy pathway. Methods C57BL/6 mice were pre-administered DEX 3 days in advance, and an abdominal exploration model was used to establish a perioperative neurocognitive disorder model. The anti-inflammatory effect of DEX was explored in vivo by detecting NLRP3-CASP1/IL-1 protein expression and behavioral testing. Primary microglia were stimulated with lipopolysaccharide (LPS) and adenosine triphosphate (ATP) in vitro, the expression of CASP1 and IL-1β was detected in the supernatant of cells, and the expression of autophagy-related proteins microtubule-associated protein 1 light chain 3 beta (MAP1LC3B) and sequestosome 1 (SQSTM1) was examined in the cytoplasm. Meanwhile, Co-immunoprecipitation (Co-IP) was used to detect NLRP3 protein ubiquitination. Results Pre-administration of DEX reduced the protein expression of NLRP3, CASP1, and IL-1 in the hippocampus of mice induced by surgery and also improved the impairment of learning and memory ability. DEX also effectively relieved the decrease in spine density of the hippocampal brain induced by surgery. DEX decreased the cleaved CASP1 expression, blocked the assembly of NLRP3–PYCARD–CASP1 complex, and also reduced the secretion of mature IL-1 in vitro. Mechanically, it accelerated the degradation of NLRP3 inflammasome via the autophagy–ubiquitin pathway and reduced the green fluorescent protein/red fluorescent protein MAP1LC3B ratio, which was comparable to the effect when using the autophagy activator rapamycin (Rapa). Furthermore, it increased the ubiquitination of NLRP3 after LPS plus ATP stimulated microglia. Conclusion DEX attenuated the hippocampal inflammation by promoting NLRP3 inflammasome degradation via the autophagy–ubiquitin pathway, thus improving cognitive impairment in mice.